INTEGRATING THE CULTURE OF ZIKIR AND SLAWATAN ON THE COMMITMENT OF THE MAULID NABI MUHAMMAD - Dini Yuli Saputri (The Pontianak State Institute of Islamic Studies, 2023)
This work examines the rituals of the Prophet Muhammad's birthday in traditional forms and neo-Soufism performances. religious leaders such as Habib Sheikh help motivate people seeking a different experience in the form of neo-Soufism practices in urban Indonesia. This work adopts participant observation and ritual theory to examine the process, actions, and performance actors such as sholawatan assembly. ideas that underlie the existence of music and the spirit of the marginal Muslim community that uses music as a symbol of existence. In addition, it also discusses philosophical conceptions in the form of practical assumptions and useful work principles as a reference for the performance of musical creativity.